Buttonscarves Branding Strategy Through Instagram to Increase Loyalty - Arifin, Rifka; Aulia, Aly (Jogjakarta Communication Conference (JCC), 2025)
This study analyzes the branding strategy implemented by Buttonscarves through Instagram to increase customer loyalty. Buttonscarves, as a premium hijab brand, optimally utilizes Instagram to strengthen branding and attract consumer attention. With a descriptive qualitative approach, data was collected through interviews and documentation. The results of the study show that Buttonscarves uses a consistent visual branding strategy, digital campaigns, collaboration with influencers, and interactive features such as Stories and Reels to increase customer engagement. This strategy is effective in strengthening brand identity, increasing engagement, and building a loyal customer base. This study provides insight into how social media can be utilized as a branding tool and marketing strategy in the fashion industry.